Validity Test of Hamstring Muscle Strength Test for Handball Athletes - Awang Firmansyah; Donny Ardy Kusuma; Agung Prijo Budijono; Heri Wahyudi; Afif Rusdiawan; Nur Lutfiatus Solikah; Andika Bayu Putro (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this study was to test the validity of hamstring muscle strength of handball athletes. A total of 30 handball athletes with categories of 15 male athletes (18.0 ± 5.1 years, weight 62.6 ± 20.7 kg, height 173.6 ± 5.0 cm, BMI 22.1 ± 4.0 kg / m2) and female (18.0 ± 5.1 years, weight 54.6 ± 17.4 kg, height 164.7 ± 6.9 cm, BMI 21.4 ± 2.2 kg/m2). No history of lower extremity injuries participated in a hamstring strength test. Hamstring strength tests are performed isometrically with ISO Prone and ISO 60 tests using nordbord tools and load cells tied using hooks called pabletest. From the test results there is a validity level of 0.000 with reliability of 0.8, so that the data can be said to be valid on both tests, namely ISO Prone and ISO 60. Load cells on pabletes are able to measure hamstring muscle strength in handball athletes. The advantages of load cells on pabletes can be made simply but not everyone can make arrangements so as to output data that can be interpreted.  Subsequent research can be done using different contractions such as eccentrics and increasing the number of research subjects more by developing better software.